The Suitability of Direct Medical Costs with INA-CBG'S Claims of Outpatient Breast Cancer in Class A and B Hospitals - Diesty Anita Nugraheni; Fanyda Amiyassin Hafi'ah; May Syahra Indah Permata Harlin; Aji Tetuko; Titik Rahayu Indarti; Gita Mayasari (Jurnal Ilmu Kesehatan Masyarakat, 2024)
BPJS Kesehatan noted that cancer financing claims reached IDR 3.5 trillion, ranking second after heart disease. This study aimed to determine the difference in direct medical costs with Indonesian-Case Base Groups (INA-CBGs) claims of outpatient breast cancer in Class A and B hospitals. The population is National Health Insurance (JKN) patients with outpatient breast cancer with the code INA-CBGs C-3-13-0. Data was collected retrospectively by tracing medical records, pharmaceuticals, and direct medical cost data for outpatient cancer patients in Class A and B hospitals for 2021. Direct medical costs are the actual costs of a patient's health care during a single visit to the hospital based on the hospital's perspective. Using the Mann-Whitney test, statistical analysis was performed to see how INA-CBGs claims differ from direct medical costs. The study result showed that the average direct medical cost of outpatient breast cancer patients in the group of recipients of contribution assistance (PBI) in Class A hospitals was IDR 3,397,073, non-PBI patients were IDR 3,439,253, and in Class B hospitals were IDR 2,619,355.26 with the direct medical cost component that contributed the most was drug bills. The direct medical costs of the hospital are more significant than the claims of INA-CBGs, resulting in a negative difference with the details of PBI patients in class A hospitals of minus IDR 88,041,600, non-PBI patients of minus IDR 91,386,300, and patients in Class B hospitals of minus IDR 160,419,079. There is a significant difference between the total claims of INA-CBG and direct medical costs for outpatient breast cancer patients in Class A and B hospitals (p=0.0001).